Rational Synthesis of Activated Carbons for Enhanced CO2 Uptake and Methane Storage - Albeladi, Nawaf (2024)
The atmospheric concentration of CO2 has reached alarming levels, primarily due to the combustion of fossil fuels. This surge in CO2 concentrations has led to rising global temperatures, increased frequency of extreme weather events, and threats to all forms of life on Earth. This scenario necessitates the urgent need to develop CO2 capture and removal technologies to ensure a more sustainable future. Moreover, the use of fossil fuels not only contributes significantly to CO2 emissions but reserves and supply are also limited. This Thesis covers themes on the rational preparation of porous carbons that are targeted at the capture of CO2 or the storage of gases (e.g. methane) that may be used as transitional energy sources towards a fossil-free economy. In this regard, ‎Chapter 1 explores the state-of-the art on potential solutions, including CO2 capture and storage via physisorption on porous materials, with a focus on readily synthesised activated carbons. Additionally, the chapter highlights the potential of methane-based natural gas as an alternative to conventional fossil fuels for vehicular transport, given its abundant reserves and lower carbon emissions. The storage of methane for vehicular use may be achieved using porous materials. However, the preparation of porous materials that meet set targets, such as those outlined by the US Department of Energy (DOE), remains a challenge. The considerations that must be carefully considered in seeking suitable materials for such gas storage applications include precise control over porosity parameters such as surface area, pore volume, pore size, and packing density. Therefore, both the ability to accurately modulate the textural properties and a comprehensive understanding of the relationship between gas (CO2 or CH4) uptake capacity and pore size are essential. This thesis is aimed to address these issues.